William Ludlam: portrait of an eighteenth-century mathematician - Decesare, Richard (Bshm Bulletin: Journal of The British Society for The History of Mathematics, 2011)
In 1785, William Ludlam wrote a book entitled The rudiments of mathematics. After I purchased the 1790 edition of this text some years ago at an antiquarian bookstore in Connecticut, I became interested in learning more about him. Ludlam's name had appeared as a footnote in several histories of mathematics, but little else had been written about him. I began some research, simply out of curiosity. What emerged was a story of an interesting mathematician, scientist, inventor, and clergyman - and a man who often found himself in the middle of controversy and subject to personal attacks, whether deserved or not. This article is a biography of Ludlam, in which I have used his own words, as well as those of his adversaries, wherever possible. © 2011 British Society for the History of Mathematics.
Keywords: dept.mat

Parental knowledge and substance use among african american adolescents: influence of gender and grade level - Tebes, Jacob Kraemer; Cook, Emily C.; Vanderploeg, Jeffrey J.; Feinn, Richard; Chinman, Matthew J.; Shepard, Jane K.; Brabham, Tamika; Connell, Christian M. (Journal of Child and Family Studies, 2011)
Parental knowledge is defined as parental awareness and information about a child's activities, whereabouts, and associations that is obtained through parental monitoring, parental solicitation, or self-disclosure. Increased parental knowledge is generally associated with lower adolescent substance use; however, the influence of various contextual factors, such as adolescent gender and grade level is not well understood, particularly for different racial or ethnic groups. In the present study, we used Hierarchical Generalized Linear Modeling analyses to examine the longitudinal relationship of parental knowledge to adolescent substance use in the context of adolescent gender and grade level among 207 urban African American adolescents in grades 6-11. Results indicated that increased parental knowledge is associated with a concurrent lower likelihood of substance use across all types of substances examined (alcohol, tobacco, marijuana, other drug use, and any drug use), but it did not predict changes in substance use 1 year later for the entire sample. However, analyses by gender and grade level showed that for boys and middle school youth, parental knowledge was a protective factor for increases in substance use across 1 year. Findings are discussed in terms of their implications for prevention and health promotion interventions for adolescent substance use among African American youth.
Keywords: African American adolescents; Developmental differences; Gender; Parental knowledge; Substance use; dept.mat

Efficient constant-velocity reconfiguration of crystalline robots** - Aloupis, Greg; Collette, S bastien; Damian, Mirela; Demaine, Erik D.; Flatland, Robin; Langerman, Stefan; O'Rourke, Joseph; Pinciu, Val; Ramaswami, Suneeta; Sacrist, Vera; Wuhrer, Stefanie (Robotica, 2011)
In this paper, we propose novel algorithms for reconfiguring modular robots that are composed of n atoms. Each atom has the shape of a unit cube and can expand/contract each face by half a unit, as well as attach to or detach from faces of neighboring atoms. For universal reconfiguration, atoms must be arranged in 2 × 2 × 2 modules. We respect certain physical constraints: each atom reaches at most constant velocity and can displace at most a constant number of other atoms. We assume that one of the atoms has access to the coordinates of atoms in the target configuration. Our algorithms involve a total of O(n2) atom operations, which are performed in O(n) parallel steps. This improves on previous reconfiguration algorithms, which either use O(n2) parallel steps or do not respect the constraints mentioned above. In fact, in the settings considered, our algorithms are optimal. A further advantage of our algorithms is that reconfiguration can take place within the union of the source and target configuration space, and only requires local communication. © 2011 Cambridge University Press.
Keywords: Algorithms; Atoms; Constant velocities; Control of robotic systems; Local communications; Mobile robots; Modular robots; Motion planning; Novel algorithm; Path planning; Physical constraints; Reconfiguration algorithm; Robot programming; Robotic systems; Robotics; Target configurations; dept.mat

A group with deep pockets for all finite generating sets - Warshall, Andrew D (Israel Journal of Mathematics, 2011)
We show that the discrete Heisenberg group has unbounded dead-end depth with respect to every finite generating set. We also show that, in contrast, it has bounded retreat depth. © 2011 Hebrew University Magnes Press.
Keywords: dept.mat